Analysis of YouTube videos about urinary catheterization technique of male delay - Flávia Barreto Tavares Chiavone; Larissa de Lima Ferreira; Pétala Tuani Candido de Oliveira Salvador; Cláudia Cristiane Filgueira Martins Rodrigues; Kisna Yasmin Andrade Alves; Viviane Euzébia Pereira Santos
Objective.To analyze the execution of urinary catheterization technique of male delay in YouTube videos. Methods. This is an exploratory research with a quantitative approach, performed using the YouTube sharing site. The search of the videos was conducted in September 2014, using the controlled descriptor "urinary catheterization". Results. 32 videos were analyzed, none were in accordance with the standards established in the literature; among the main errors highlight the absence of hand washing (78.1%), the absence of the medical recording (71.8%), the absence of cleaning and drying of the patient at the end of the procedure (71.8%), the incorrect technique during antisepsis (62.5%) and the absence of gloves changes (59.3%). Conclusion. Although the YouTube sharing video site is currently a widespread tool, there is an absence of videos that reproduce the technique according to what is recommended in the literature.